1993
DOI: 10.1161/01.cir.88.5.2359
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of endogenous adenosine attenuates myocardial 'stunning' independently of coronary flow or hemodynamic effects.

Abstract: This study demonstrates that (1) administration of an adenosine deaminase inhibitor plus a nucleoside transport blocker is remarkably effective in augmenting myocardial adenosine levels during regional ischemia and subsequent reperfusion in vivo, (2) this augmentation of adenosine results in a significant and sustained attenuation of myocardial stunning, and (3) the attenuation of stunning is not due to ATP repletion or to nonspecific actions on hemodynamic variables or coronary flow. These findings suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…For example, quantitation of basal adenosine level can give accurate feedback to surgeons in cardioprotective dosing finding studies of either adenosine [36][37][38][39][40][41][42] or adenosine modulators [4,5,17,43,44], as well as help explain clinical outcome with other cardioprotective measures.…”
Section: Stabilitymentioning
confidence: 99%
“…For example, quantitation of basal adenosine level can give accurate feedback to surgeons in cardioprotective dosing finding studies of either adenosine [36][37][38][39][40][41][42] or adenosine modulators [4,5,17,43,44], as well as help explain clinical outcome with other cardioprotective measures.…”
Section: Stabilitymentioning
confidence: 99%
“…In this situation, a reduction in irreversible injury will impact on conventional measures of stunning (myocardial contractility and arrhythmogenesis). Nonetheless, postischemic contractility is enhanced by exogenous and endogenous adenosinergic stimuli under conditions of limited or no detectable cell death (149,161,165,200,201,210,215,234,235,246,258,318). In addition, recent work has identified differential effects of adenosine (77,228) and adenosinergic preconditioning (226) on oncosis versus contractile function, supporting amelioration of both injuries via different pathways.…”
Section: Protection Against Reversible Versus Irreversible Injuries Mmentioning
confidence: 99%
“…The purine nucleoside adenosine was attributed with cardioregulatory functions almost 75 years ago (64), and since then has emerged as a crucially important control substance in essentially every tissue of the body. In the heart adenosine not only plays a role in regulating growth and differentiation, angiogenesis, coronary blood flow, cardiac conduction and heart rate, substrate metabolism, and sensitivity to adrenergic stimulation (23, 67,68,73,74,260,271,283), but may play a role as an endogenous determinant of ischemic tolerance (189,225,245,259,311,312,318). From a therapeutic viewpoint, adenosine-based therapies protect against ischemic injury in a variety of animal models (72,177,208,265,288) and in human cardiac tissue (34,36,37,240,296).…”
mentioning
confidence: 99%
“…(2) stimulation of adenosine A 1 -receptors; (3) stimulation of ATP-dependent potassium channels; (4) blockage of slow calcium channels [12]; (5) frequency-dependent depression of the AV nodal conduction and depression of sinoatrial node excitation [5,6,25] and reduction of myocardial oxygen consumption [26]; (6) enhancement of myocardial glucose metabolism [26]; (7) inhibition of complement activation and adhesion of neutrophils to endothelial cells [2]; (8) platelet activation; (9) blockage of the xanthine oxidase pathway of free radical generation [9,10]; and (10) blockage of catecholamine responsiveness [23].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, this mechanism was demonstrated to be especially valuable in the management of supraventricular tachycardia, as well as for the control of ventricular heart rate in cases of atrial flutter or fibrillation [5] and ischemia-induced ventricular fibrillation [6]. Even though various experimental and clinical studies have confirmed an improvement in the recovery of cardiac function after the application of both substances as a pretreatment for various forms of ischemia and reperfusion [2,3,4,6,7,8,9,10,11,12], information about the quality of these substances as additives to cardioplegic solutions is scarce [11].…”
Section: Introductionmentioning
confidence: 99%